Conceptions associated with sense of belonging in different school placements for Finnish pupils with special education needs. Issue 1 (2nd January 2016) - Pesonen, Henri; Kontu, Elina; Saarinen, Minna; Pirttimaa, Raija
Abstract: The aim of this study was to examine conceptions associated with sense of belonging (SEBE) in Finnish general and special school placements for pupils with special education needs. Five pupils were selected for this study by means of purposive sampling. They had a history of several school placements prior to arriving at their current special school. Qualitative phenomenographic analyses of interview transcripts revealed numerous conceptions regarding the pupils' SEBE in the different educational placements. The pupils had undergone numerous placements in which their SEBE had been jeopardised, as disturbing relationships with teachers and peers seemed to have affected the pupils' mental and physical well-being, resulting in disturbing behaviours in their earlier educational settings. Despite the various placements and issues of ableism, stigmatisation and exclusion, the pupils felt 'better' in their current, special, school with a positive climate. Furthermore, the findings of this study provided an initial exploration of the phenomenon, as well as shed light on the several limitations encountered. Hence, further exploration of school cultures and the role of teachers' values and beliefs is needed for a better understanding of how to create a school climate that supports SEBE for all pupils.